Student-centred photovoice as a mechanism for home-school interaction: Teacher perceptions of efficacy. (February 2020) - McKernan, Christine; Gleddie, Douglas; Storey, Kate
Objective: The school and home environments play a significant role in shaping the health behaviours of children. Understanding students' home environments is essential for teachers to recognise and meet their students' needs, while collaborative partnerships between the school and home have been shown to result in academic success and improved behaviour management. This study explores the unique features of photovoice as a student-centred approach to understanding the links between the school and home environments, and its feasibility to be implemented independently by teachers in the classroom. Design: Descriptive qualitative method. Setting: A Project Promoting healthy Living for Everyone in Schools (APPLE Schools) is a school-based health promotion project being conducted in 70 school communities across northern Alberta, Northwest Territories, and Manitoba, Canada. Method: One-on-one interviews with teachers who were involved in an initial photovoice project ( n = 3) and researcher field notes from observations conducted over a period of 8 months were used. Data were analysed using latent content analysis. Results: Strengths, limitations and future directions of photovoice were identified. The strengths of using photovoice included genuine student participation, strengthened communication between the school and home, and the ability to address multiple learning domains. Limitations were cost, privacy and parental support. Teachers shared promising ideas about photovoice being used for health promotion advocacy. Conclusion: Photovoice can be used by teachers as tool to strengthen the relationship between the home and the school environments. Future use of photovoice in schools is encouraged.